The econometric model for assessing the economic category of a Russian farmer entrepreneur in terms of the "Innovator vs. Conservative" system - Semin, Alexander; Kislitskiy , Mikhail (Journal of Eastern European and Central Asian Research (JEECAR), 2020)
The slowdown in agricultural growth in Russia determines the development of an innovation base for expanding exports. Therefore, the formation of a new social class of farmers-entrepreneurs, focused on the implementation of innovative activities, becomes relevant. The aim of the study was to develop an econometric model for assessing the economic types of farmers-entrepreneurs according to the system “innovator versus conservative” using the example of the agro-industrial complex. The questionnaire method was used to determine the levels of innovative development of the respondents. The survey was conducted from October 2017 to December 2019; 900 farmers from Tver, Kursk, Tambov, Penza, Arkhangelsk, Kurgan, Leningrad regions, as well as Yakutia took part in it. Using the method of cluster analysis, all classes (categories) of farmers-entrepreneurs are determined by the level of innovation. Depending on the type of enterprise, classification functions of farmers have been developed